The Influence of Perceived Role of Government on Energy Efficiency Improvement: Evidence from Manufacturing Firms in Malaysia. (August 2022) - Heng, Helen Lee Siew
Energy efficiency improvement is one of the effective strategies to attain energy sustainability. Firms' perceptions and attitudes towards energy efficiency improvement have come to be seen as vital in the supply and demand management of energy. This research aims to examine the influence of perceived role of government on manufacturing firms' intentions to improve energy efficiency. Data were collected from a survey, and the research model was empirically tested. Results from the empirical analysis show that perceived role of government significantly influenced manufacturing firms' intentions to improve energy efficiency. In addition, the results indicate that there was a significant mediating effect of attitude towards energy efficiency improvement on the relationship between perceived role of government and manufacturing firms' intentions to improve energy efficiency. Several notable policy implications can be drawn from the research results. JEL Codes: D22, L60, Q48